Correction: Lee, J.; Kang, Y. A Dynamic Algorithm for Measuring Pedestrian Congestion and Safety in Urban Alleyways. ISPRS Int. J. Geo-Inf. 2024, 13, 434 - Jiyoon Lee; Youngok Kang (ISPRS International Journal of Geo-Information)
We would like to address and correct errors found in the original publication of our article [...]